FEATURES OF THE LOGISTICS PROCESS IN THE WAREHOUSE - REZNIK NADIІA; CHORNENKA, LIUDMYLA; KRAVTSOV, ANDRII (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In modern conditions of integration of Ukraine’s economy into the world community effective functioning of enterprises is impossible without improving the organization of logistics processes. Dynamic development of economic relations leads to a significant increase in the needs of enterprises in warehouses. Warehousing problems arise and are solved at all stages of the movement of goods and material flow. Warehouses are one of the most important elements of the logistics system, however, the domestic food industry is not carefully studied, as well as issues of optimization of warehousing, which necessitates a more detailed study of this issue. The dynamic development of various sectors of the economy causes a number of problems associated with the formation of warehousing of an individual enterprise. It is expedient for small and medium-sized enterprises to organize their own warehousing facilities, and large ones to transfer warehousing functions to logistics companies. The largest Ukrainian logistics companies offer warehouses for rent, take goods for safekeeping without the right to manage goods flows, and also perform a full range of logistics services (purchase / storage / distribution with the right to manage). In the first and second case, the application of logistics principles significantly reduces the costs of the enterprise associated with the organization of warehousing processes. However, the specialized literature does not sufficiently reflect and describe the processes of warehouse formation and functioning as an element of logistics. In the Ukrainian economic literature at present there is no consensus on the development and formation of warehousing on the basis of logistical principles. Analysis of the organization of logistics processes in the warehouse enterprises. Research of the effective functioning of the logistics process and development of solutions to improve it.